Health-Related Quality of Life in Gilles de la Tourette Syndrome: A Decade of Research - Andrea Eugenio Cavanna; Kate David; Valentina Bandera; Cristiano Termine; Umberto Balottin; Anette Schrag; Caroline Selai (Behavioural Neurology, 2013)
Gilles de la Tourette syndrome (GTS) is a neurodevelopmental condition characterised by multiple motor and phonic tics and associated behavioural problems, carrying a significant burden on patients' lives. Although the term health related-quality of life (HR-QOL) has only been used in recent years, several studies have long addressed the impact of GTS on physical, psychological and social aspects of wellbeing of both children and adults with GTS. We set out to answer the question "Is HR-QOL affected by GTS and, if so, in what domains?" by conducting a systematic literature review of published original studies addressing HR-QOL in both children and adult patients with GTS. This review focuses on the current evidence on the impact of GTS on patients' lives, mainly informed by studies using generic functional impairment and HR-QOL measures from the last decade, and expands on the new opportunities introduced by the recently developed GTS-specific HR-QOL scales (GTS-QOL and GTS-QOL-C&A). Analysis of the first decade of studies specifically addressing HR-QOL in GTS suggests that co-morbid conditions are key factors in determining HR-QOL in young patients, whilst the picture is more complex in adults with GTS. These findings offer some general directions for both current clinical practice and future research.